2018
DOI: 10.1007/s11095-018-2427-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined Used of Rheology and LF-NMR for the Characterization of PVP-Alginates Gels Containing Liposomes

Abstract: The rheological and LF-NMR characterization were confirmed and supported by the independent techniques TEM, cryo-TEM and release tests Thus, our findings reiterate the potentiality of both rheology and LF-NMR for the characterisation of soft materials such as interpenetrated polymeric networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…This is because the conventional methods were based on three common assumptions that are: (1) no-slippage on the boundary; (2) homogeneous velocity profile of the bulk during shear; (3) relaxation upon shear cessation occurring without the emergence of macroscopic motion due to shear history [86]. Guilia Fanesi et al (2018) demonstrated the potentiality of using rheology and low-frequency magnetic resonance imaging for the characterization of hydrogels [87].…”
Section: Properties and Structurementioning
confidence: 99%
“…This is because the conventional methods were based on three common assumptions that are: (1) no-slippage on the boundary; (2) homogeneous velocity profile of the bulk during shear; (3) relaxation upon shear cessation occurring without the emergence of macroscopic motion due to shear history [86]. Guilia Fanesi et al (2018) demonstrated the potentiality of using rheology and low-frequency magnetic resonance imaging for the characterization of hydrogels [87].…”
Section: Properties and Structurementioning
confidence: 99%
“…LF-NMR characterization implies the introduction of a 1-2 mL of blend in NMR tube, then analysis proceeds and the output consist in the magnetization decay (I(t)) due to the magnetic relaxation of hydrogens belonging to water molecules contained in the sample. Then, I(t) is fitted by means of a sum of decaying exponentials, each one characterized by a different time decay constant (T 2i ) and weight (A i ) (Abrami et al, 2018;Fanesi et al, 2018):…”
Section: Lf-nmr Measurementsmentioning
confidence: 99%
“…(A.1) and (A.2) in Appendix A. Another non-ideal feature of hydrogels, which is not considered in the equation Peppas-Merrill, is spatial gel inhomogeneity, as hydrogels always exhibit an inhomogeneous crosslink density distribution (Abrami et al, 2018;Fanesi et al, 2018). While crosslink density of hydrogels can be described by rheological measurements, the gel inhomogeneity can be effectively determined by LF-NMR analysis (Fanesi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Na-Alg/PVP NMR, CLSM, TEM, DLS optimize IPN hydrogels devoted to the release of active agents. [59] Na-Alg/Fenugreek seeds/Psyllium Seed PCR, OM enhancement of probiotic bacterial growth in the gastrointestinal environment. [60] Na-Alg/methylcellulose Hmsc, SEM, CLSM improve the functionality of the plotted cell-matrix constructs.…”
Section: Blends and Composite Of Na-algmentioning
confidence: 99%